The Effectiveness of Scirpus grossus and Limnocharis flava as Fitoremediation Agents of Nitrate-Phosphate to Prevent Microcystis Blooming in Fresh Water Ecosystem - Aliyah Siti Sundari; Catur Retnaningdyah; Suharjono (Journal of Tropical Life Science, 2013)
The aim of this study was to reduce the concentration of dissolved nitrate-phosphate, because it can prevent the occurrence and inhibit the growth of Microcystis bloom waters. The study was conducted experimentally in the laboratory. The Microcystis isolation was carried out in Sutami Reservoir. Then, remediation treatment with hydromacrophyte (Scirpus grossus, Limnocharis flava and combination of both hydromicrophyte) were done during the 15 day incubation period. Abiotic factors were measured on day 0, 6, 12 and 15, but the abundance of Microcystis cells was counted daily. The productivity of hydromacrophyte was measured at the end of the research. The research results showed that hydromacrophytes were effective to reduce nitrate and phosphate concentrations. The combination of S. grossus and Microcystis reduced nitrate concentration up to 99.89 %, while the highest reduction of dissolved phosphate (98.22 %) was resulted from the combination of L. flava and Microcystis. The combination treatment of L. flava and S. grossus was capable to prevent Microcystis growth rate and produced the carying capacity of 65 cells.L-1.day-1 and 6.93 x 104 cells/mL.